Commissioning community-based art projects to support engagement with nature-based solutions - Acker, Maleea; Dubrawski, Kristian Lukas; Tremblay, Crystal; Brill, Gregg; Creates, Marlene; Hash, Colton; Robinsong, Erin; Howard, Annabel (Frontiers in Sustainability, 2025)
Understanding social-ecological connection is paramount to adoption and long-term viability of nature-based solutions (NbS). Here, we describe a three-year trial of community-engaged participatory research (CBPR) through an artist commission program run by Engage with Nature-based Solutions (http://www.engagewithnbs.ca). The program has thus far commissioned twelve Canadian artists to contribute their artistic research to facilitate conversations about climate change and conceptualizations of NbS. The artists we commissioned created a piece of art for their local community on NbS and climate, facilitated a community-engaged workshop to share their research creation, and supported the development of an online toolkit meant to help other communities engage with NbS and climate change. We suggest that this commission program is a cost-effective way to: (i) reach a diversity of communities typically outside the reach of academia, (ii) enlarge audiences who are engaged with NbS, (iii) provide alternative formats and mediums for engagement and education on NbS, (iv) give credence to artistic work as climate work, and (v) provide opportunities for collaboration between the arts/sciences and community/academia.